Machine Learning Based Alzheimer’s Disease Detection in MRI Images - S, Anil N; M, Bharghavi; J, Chandrika K; B, Divyashree L; N, Hema K (Perspectives in Communication, Embedded-systems and Signal-processing - PiCES, 2021)
Magnetic Resonance Image is a medical imaging technique which can be used to diagnose problems associated with brain. The advantage of this technique is that it is completed contactless – no need to do any surgery to know what’s wrong with the brain. This paper shows different ways through which Dementia can be diagnosed, all by using MRI images and computer vision. Also in this paper, a machine learning based method is proposed to identify Alzheimer’s disease.